Diaphragm dysfunction : Facts for clinicians - Bruells, C S; Marx, G (Medizinische Klinik, Intensivmedizin und Notfallmedizin, 2018)
Diaphragm function is crucial for patient outcome in the ICU setting and during the treatment period. The occurrence of an insufficiency of the respiratory pump, which is predominantly formed by the diaphragm, may result in intubation after failure of noninvasive ventilation. Especially patients suffering from chronic obstructive pulmonary disease are in danger of hypercapnic respiratory failure. Changes in biomechanical properties and fiber texture of the diaphragm are further cofactors directly leading to a need for intubation and mechanical ventilation. After intubation and the following inactivity the diaphragm is subject to profound pathophysiologic changes resulting in atrophy and dysfunction. Besides this inactivity-triggered mechanism (termed as ventilator-induced diaphragmatic dysfunction) multiple factors, comorbidities, pharmaceutical agents and additional hits during the ICU treatment, especially the occurrence of sepsis, influence diaphragm homeostasis and can lead to weaning failure. During the weaning process monitoring of diaphragm function can be done with invasive methods - ultrasound is increasingly established to monitor diaphragm contraction, but further and better powered studies are in need to prove its value as a diagnostic tool.